1995
DOI: 10.1007/bf02286445
|View full text |Cite
|
Sign up to set email alerts
|

Structure and conformation of 1-Bromopropane: A gas-phase electron-diffraction investigation using microwave-spectroscopy data and results from ab initio calculations as constraints

Abstract: 1-Bromopropane has been studied by gas-phase electron diffraction (ED) at 24~ Earlier published values for rotational constants from microwave spectroscopy (MW), together with results from ab initio molecular-orbital calculations, have been included in the ED analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Thus Morino and Kuchitsu studied, by electron diffraction spectroscopy, the conformation of 1-propyl chloride, CH 3 CH 2 CH 2 Cl, and found that the gauche conformer is favored, though slightly. 8,94 Hirota obtained a similar result for 1-propyl fluoride, CH 3 CH 2 CH 2 F. 9 Similar conclusions were reported by far-infrared and low-frequency Raman, 95 electron diffraction, 96 FT-IR, 97 and X-ray photoelectron spectroscopy. 90 In every case, the gauche conformation has been found to be preferred.…”
Section: Conformation Of Alkyl Halidessupporting
confidence: 62%
“…Thus Morino and Kuchitsu studied, by electron diffraction spectroscopy, the conformation of 1-propyl chloride, CH 3 CH 2 CH 2 Cl, and found that the gauche conformer is favored, though slightly. 8,94 Hirota obtained a similar result for 1-propyl fluoride, CH 3 CH 2 CH 2 F. 9 Similar conclusions were reported by far-infrared and low-frequency Raman, 95 electron diffraction, 96 FT-IR, 97 and X-ray photoelectron spectroscopy. 90 In every case, the gauche conformation has been found to be preferred.…”
Section: Conformation Of Alkyl Halidessupporting
confidence: 62%
“…Examples of the former were aniline [23], ethynylbenzene [24], tetramethylsilane [25], and pbis(trimethylsilyl)benzene [26]. Examples of the more complicated structures were octamethylcyclotetrasilane [27], 1-bromopropane [28], 1-chlorobutane, 1-bromobut ane, and 1-iodobutane [29], 1,2,4,5-tetracyanobenzene [30], tert-butylazide [31], some cyclic nitramines [32], 1,3,5-tris(trimethylstannyl)benzene [33], tris(pyrazol-1-yl)-s-triazine [34], and 1,1-dimethylsilacyclopentene-3,4-oxide [35]. The growing literature even in such a relatively small field as gas-phase electron diffraction necessitated a database [36] to help making structural information available for potential users.…”
mentioning
confidence: 99%